Developmental Disabilities : Molecules Involved, Diagnosis, and Clinical Care - Salehi, Ahmad; Salehi, Ahmad (IntechOpen, 2013)
Although various developmental disabilities affecting children and adults might have different pathogeneses, underlying mechanisms, and clinical presentations, the current books emphasizes the fact that there are numerous commonalities in methods of understanding, clinical diagnosis, and handling of behavioral abnormalities in affected individuals. For instance, understanding sexual maturation and its consequences in people with intellectual disability would certainly present a path to better understanding of the differences with controls and more effective handling of the unwanted consequences in people affected.
English
Keywords: Neurosciences; Neurosciences